Determining customer satisfaction: a case study of a tourism establishment in the Vaal region - Cilliers, Charmaine Danielle (My University, 2018)
Tourism is an extremely important sector in any economy of a country and is a package of combined services and goods. There are a variety of types of tourism, and tourism also has a variety of sectors and characteristics. Customer satisfaction is very important within any organisation, because it provides a variety of benefits. The Kano model and many theories assist in understanding customer satisfaction and the factors that better influence the satisfaction of the customers. To accurately measure the satisfaction of customers, there are a variety of guidelines to follow to develop a well-developed questionnaire. The main goal of this study was to determine customer satisfaction and the factors that contribute to customer satisfaction, based on a case study at a tourism establishment (accommodation establishment) in the Vaal Region. The objectives were to conduct a literature review to identify the factors that affect customer satisfaction at an accommodation establishment and develop a measuring instrument to determine customer satisfaction at an accommodation establishment. Furthermore, an empirical analysis was conducted to measure the level of performance of the identified factors at an accommodation establishment in the Vaal Region. Additionally, to determine the factors that contribute to the satisfaction of the customers at a specific accommodation establishment in the Vaal Region. Thereafter, determine the difference between the factors that are regarded as important contributors to customer satisfaction and the factors with which customers are satisfied with at an accommodation establishment. Moreover, determine the difference between customer satisfaction factors across trip-related and demographic variables at an accommodation establishment. Finally, recommendations were made regarding the empirical results and for future research. The research followed a case study approach using quantitative, exploratory and descriptive research to administer and test the questionnaire, and to evaluate the satisfaction of the customers. Furthermore, the study used a non-probability method, convenience sampling. The sample size of the study was 132 customers at the accommodation establishment and a questionnaire was used to measure the satisfaction of the customers. The results indicated that the majority of the respondents were totally satisfied with certain aspects at the accommodation establishment. In total 11 factors were identified that contribute to customer satisfaction, and a total of 10 factors were identified that influence the satisfaction level of the customers. There was a statistical significant correlation between the factors with which customers are satisfied with, the factors that the customers regard as important, other trip-related and demographic variables. It can be seen that the accommodation establishment must take into account the factors which influence customer satisfaction to obtain higher customer satisfaction by.
M.Tech (Department of Tourism Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: tourism sector, hospitality, customer satisfaction, customer relations and measuring instrument; Customer satisfaction -- Vaal Triangle.; Tourism -- Vaal Triangle.